Factors Influencing Burnout Syndrome in Obstetrics and Gynecology Physicians - Iorga, Magdalena (Biomed Res Int, 2017)
AIM: To identify the influence of environmental, personality, and alexithymia factors on burnout syndrome among obstetrics and gynecology physicians. MATERIAL AND METHODS: A total of 116 physicians (35 men and 81 women) completed questionnaires and sociodemographic data sheets. The Maslach Burnout Inventory, the Big Five Inventory, and the Toronto Alexithymia Scale were used to measure burnout, innate personality traits, and alexithymia, respectively. The t-test and Pearson correlations were used for other measurements. RESULTS: Of the 116 study physicians, 12.9% have suffered or still suffer from depression and 35.3% have had or still have problems related to insomnia. Regarding emotional exhaustion and depersonalization factors, men obtained lower scores than women (18.73 ± 13.48 versus 24.14 ± 11.71 for emotional exhaustion; 5.97 ± 5.45 versus 7.70 ± 5.29 for depersonalization). Self-reported depression was related to higher scores for all 3 domains, to higher total scores for alexithymia and neuroticism, and to lower scores for extraversion, conscientiousness, and openness. Residents and consultants had markedly different scores. CONCLUSION: The results of this study will help obstetrics and gynecology physicians cope with professional burnout and to consider personality traits, alexithymia domains, and environmental factors when finding strategies to cope with their professional stress.